A Low Profile, Broadband Linearly and Circularly Polarized Cavity Backed Antenna Using Halved-Dual Mode SIW Cavity - Razavi, Seyed A.; Neshati, Mohammad H. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a low profile single fed cavity backed slot antenna producing both linear and circular polarizations at two different frequency is presented using a halved dual mode cavity. The proposed antenna has a planar structure using a single layer of printed circuit board (PCB) which allows for integrating the antenna to other planar circuits and provides straight forward connection to SMA connector. One prototype of the antenna is designed and fabricated and very good agreement between measurement and simulation results are obtained. Results show that the proposed antenna is able to present suitable radiation characteristics as both linearly polarized (LP) antenna and circularly polarized (CP) antenna.